Amphiascoides neglectus (Copepoda: Harpacticoida) as diet for aquarium corals cultured under laboratory condition - Hasnan, Hazwani H.; Wan Sulaiman, Wan Mohd. Azizi; Ahmad, Zuhairi; Wan Rasdi, Nadiah; Kassim, Zaleha (BIOFLUX SRL, 2019)
The main issue in coral aquaculture is the identification of suitable food that can speed up the growth and supply enough nutrients. While copepods can be found in coral ecosystem, the study of its contribution in coral growth is far from mature. A series of feeding experiment was therefore carried out to investigate the effect of copepod diet (Amphiascoides neglectus) on coral growth under laboratory conditions. The feeding of coral (Protopalythoa sp., a soft coral and Acropora sp.) on A. neglectus nauplii was examined for seven days to investigate the feeding preference time. Overall, there was no significant effect of feeding times between groups (am and pm) as shown by the F-test result where the p-value was p = 0.260 (p > 0.05). From tests of between-subjects effects, there was no significant difference of mean feeding on corals between two different feeding times (p = 0.312) regardless of day. The coral growth was measured (increase of size) for five weeks. Overall comparisons between two groups on different types of feeds (A. neglectus nauplii and mixed copepods) were analyzed over coral growth. There was no significant difference in growth as shown by the F-test where the p-value was p = 0.794 (p > 0.05). From tests of between-subjects effects, there was no significant difference in mean coral growth between two different types of copepods (p = 0.579) regardless of week. Results indicate the suitability of cultured copepod A. neglectus to maintain corals in captivity with less procedure and more cost effective